2008
DOI: 10.1037/0012-1649.44.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Adult romantic relationships as contexts of human development: A multimethod comparison of same-sex couples with opposite-sex dating, engaged, and married dyads.

Abstract: This article presents a multimethod, multi-informant comparison of community samples of committed gay male (n=30) and lesbian (n=30) couples with both committed (n=50 young engaged and n=40 older married) and noncommitted (n=109 exclusively dating) heterosexual pairs. Specifically, in this study the quality of same- and opposite-sex relationships was examined at multiple levels of analysis via self-reports and partner reports, laboratory observations, and measures of physiological reactivity during dyadic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 54 publications
4
80
0
1
Order By: Relevance
“…This suggests that adult attachment patterns have similar important consequences for relationship views in LGB samples as they do in heterosexual samples, consistent with past research that highlights the similarities in the fundamentals of romantic relationships of LGB and heterosexual couples (Kurdek, 2002;Mohr, 2008;Roisman, Clausell, Holland, Fortuna, & Elieff, 2008).…”
supporting
confidence: 74%
“…This suggests that adult attachment patterns have similar important consequences for relationship views in LGB samples as they do in heterosexual samples, consistent with past research that highlights the similarities in the fundamentals of romantic relationships of LGB and heterosexual couples (Kurdek, 2002;Mohr, 2008;Roisman, Clausell, Holland, Fortuna, & Elieff, 2008).…”
supporting
confidence: 74%
“…Interestingly, a recent study noted that single gays and lesbians reported higher psychological distress (i.e., internalized homophobia, depressive symptoms, and stress) and a lower sense of well-being (i.e., the presence of meaning in life) than individuals in committed or legally-recognized same-sex relationships (Riggle et al, 2010). The quality and intimacy associated with heterosexual marriages are often not distinguishable from that which is observed in committed same-sex couples (Roisman et al, 2008). This may explain the fact that the lack of a strong social tie in humans that usually manifest in adults seems universally detrimental to mental health.…”
Section: Hpa Axis and Stress-related Psychopathologiesmentioning
confidence: 92%
“…In fact, as summarized by Kurdek (2005) and Peplau and Fingerhut (2007), married heterosexual couples and same-sex couples generally report equivalent levels of relationship satisfaction, whereas same-sex couples appear to have more equitable division of household labor and more constructive conflict resolution. More recently, Roisman, Clausell, Holland, Fortuna, and Elieff (2008) demonstrated that married heterosexual and committed same-sex couples were indistinguishable on multiple measures of relationship quality, whereas Balsam and colleagues (2008) found that same-sex couples report higher relationship quality, compatibility, and intimacy and less conflict than did married heterosexual couples. Nevertheless, same-sex unions appear to be less stable than heterosexual marriages.…”
Section: Introductionmentioning
confidence: 94%
“…However, because existing programs were overwhelmingly designed for and tested on first-marriage heterosexual couples, it is unclear whether they are appropriate for use with individuals in same-sex unions. On one hand, a small but growing literature suggests that same-sex relationships are highly similar to heterosexual relationships along numerous dimensions, including relationship satisfaction and quality (Roisman et al, 2008), couple communication patterns ( Julien, Chartrand, Simard, Bouthillier, & Begin, 2003), and relationship change over time (Kurdek, 2004). Moreover, the predictors of relationship satisfaction and stability appear to be consistent across same-sex and heterosexual couples (Gottman et al, 2003;Kurdek, 2004;Peplau & Fingerhut, 2007).…”
Section: Introductionmentioning
confidence: 95%